Implementation of Pancasila Student Profile in Islamic Religious Education Learning - Raharja, Shafira Laeliocattleya; Inayati, Nurul Latifatul (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to describe the implementation of the Pancasila Student Profile in Islamic religious education at Junior High 9 Surakarta, as well as to identify the challenges faced and the measures taken by islamic religious education teachers to address them. A qualitative descriptive method was employed using data collection techniques including observation, interviews, and documentation. The findings indicate that the implementation of the Pancasila Student Profile in islamic religious education at Junior High School 9 Surakarta occurs both inside and outside the classroom. Inside the classroom, islamic religious education teachers employ project-based learning, discussions, and creative assignments such as decorating students' work and displaying it in the classroom, as well as reciting the Asmaul Husna and Quranic recitation. Outside the classroom, activities include habitual prayer, mid-morning prayer, noon prayer, Friday prayer, and regular study sessions. Challenges encountered in this implementation include limited classroom implementation time, students' insufficient awareness of the significance of Pancasila values and religious teachings in daily life, and constraints related to facilities and instructional media availability such as limited teaching aids and media resources.